2007
DOI: 10.4049/jimmunol.179.5.2741
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Decreases p53 Protein to Prolong Survival of Airway Epithelial Cells

Abstract: Respiratory syncytial virus (RSV) is a clinically important pathogen. It preferentially infects airway epithelial cells causing bronchiolitis in infants, exacerbations in patients with obstructive lung disease, and life-threatening pneumonia in the immunosuppressed. The p53 protein is a tumor suppressor protein that promotes apoptosis and is tightly regulated for optimal cell growth and survival. A critical negative regulator of p53 is murine double minute 2 (Mdm2), an E3 ubiquitin ligase that targets p53 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 47 publications
4
44
1
Order By: Relevance
“…In fact, Nutlin-3A administration significantly increased the survival of mice following LPS-induced septic shock (E. A. Komarova, L. Vassilev, and A. V. Gudkov, in preparation). These results are consistent with earlier reports by Liu et al 81 and Groskreutz et al, 101 who showed anti-inflammatory effects of Nutlin-3A in models of LPS-induced and respiratory syncytial virus-induced lung injury, respectively. It was shown previously in vitro that Nutlin-3A can down-regulate TNFα-and IL-1-induced activation of NF-κB-dependent reporter gene expression and inhibit the expression of proteins encoded by the NF-κB target genes ICAM-1 and MCP-1, which are known to be critical for cancer cell invasion.…”
Section: Monographssupporting
confidence: 83%
“…In fact, Nutlin-3A administration significantly increased the survival of mice following LPS-induced septic shock (E. A. Komarova, L. Vassilev, and A. V. Gudkov, in preparation). These results are consistent with earlier reports by Liu et al 81 and Groskreutz et al, 101 who showed anti-inflammatory effects of Nutlin-3A in models of LPS-induced and respiratory syncytial virus-induced lung injury, respectively. It was shown previously in vitro that Nutlin-3A can down-regulate TNFα-and IL-1-induced activation of NF-κB-dependent reporter gene expression and inhibit the expression of proteins encoded by the NF-κB target genes ICAM-1 and MCP-1, which are known to be critical for cancer cell invasion.…”
Section: Monographssupporting
confidence: 83%
“…Thus, viral RNA mimetics are advantageous for analyzing the basic principles of antiviral responses as revealed in our study. It is important to note that RIG-I and MDA-5 are capable to induce apoptosis independently of two key antiviral proapoptotic pathways, the type I IFN system and p53 (37,38). As a consequence, apoptosis induction by RIG-I and MDA-5 remains functional even in situations where the virus applies strategies to downregulate type I IFN (11,39) or p53 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results suggest that induction of apoptosis in these syncytia is FMG-and cell line-dependent and is certainly not the unique mechanism involved in syncytial death. It has been shown that Respiratory Syncytial Virus can block early apoptosis of infected cells through a p53-dependent pathway and phosphatidyl inositol-3kinase/AKT activation, 38 while its F fusogenic protein is capable of inducing p53-dependent apoptosis. 39 The presence or absence of the p53 tumorsuppressor protein may thus contribute to explaining the differences we observed between the two NSCLC cell lines A549 (P53 WT) and H322 (p53À/À) in response to GALV-induced syncytia death.…”
Section: Fmg-mediated Tumor Therapy E-h Lin Et Almentioning
confidence: 99%